Climate change as a wildlife health threat: a scoping review - Sabrina S. Greening; Lucie R. Pascarosa; Avery L. Munster; Roderick B. Gagne; Julie C. Ellis (BMC Veterinary Research)
Abstract Background The definition of wildlife health continues to expand with the recognition that health is more than the absence of disease. Practitioners are working to integrate concepts such as vulnerability, adaptation, and resilience into wildlife health research, surveillance, and management actions. Here, we performed a scoping review to identify scholarly articles from 2008 onwards with a focus on climate change impacts on wildlife health. Searches were conducted in Web of Science, Zoological Record, Scopus, Ovid CAB Abstracts, and ProQuest Dissertations and Theses. Articles were screened for relevance and fed into an AI-based thematic analysis that identified recurring themes across the literature. Each theme was manually reviewed and refined to help describe the scope and depth of existing literature, identify key themes, and assess potential knowledge gaps. Results In total, 2,249 citations were retrieved of which 372 were included in further analysis after applying a set of inclusion/exclusion criteria. On closer inspection, 30.4% (113/372) of the papers were focused on climate-associated impacts on vector distribution. For this reason, two thematic analyses were performed, one which only included the subset of papers focused on climate change and vector distribution (n = 113) and another including the remaining papers focused on climate-associated impacts on wildlife health (n = 259). Amongst the subset of papers focused on vector distribution, top themes included concepts related to pathogen transmission dynamics, human/public health, and pathogen prevalence, while health papers focused on concepts related to increasing temperatures, species home ranges and distribution, and changing environmental variables. Conclusions A large number of the papers retrieved in the literature search focused on how climate change impacts the distribution and abundance of host, vector, and pathogen species, remaining disease-centric in their approach. Papers including themes related to management actions were limited reflecting some uncertainty on how best to respond and prepare for climate change. Further discussion is needed on how wildlife health concepts can be used to help inform on-the-ground management actions in the face of climate uncertainty, this includes the collection of baseline health data and research into health metrics that could be used as indicators of resilience at the ecosystem level.